2013
DOI: 10.1007/s13762-013-0402-1
|View full text |Cite
|
Sign up to set email alerts
|

The role of biodegradable particulate and colloidal organic compounds in biological nutrient removal activated sludge systems

Abstract: The efficiency of denitrification and enhanced biological phosphorus removal in biological nutrient removal activated sludge systems is strongly dependent on the availability of appropriate carbon sources. Due to high costs of commercial compounds (such as methanol, ethanol, acetic acid, etc.) and acclimation periods (usually) required, the effective use of internal substrates is preferred. The aim of this study was to determine the effects of slowly biodegradable compounds (particulate and colloidal), as inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 37 publications
1
16
0
Order By: Relevance
“…Sample results and model predictions of batch experiments are presented in Figure 2 a-b [4,6]. Set of the process stoichiometric and kinetic parameters in ASM2d was used as a base point of further process calibration in newly developed comprehensive model Mantis2 for simulation study of "virtual" plant layout in GPS-x (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Sample results and model predictions of batch experiments are presented in Figure 2 a-b [4,6]. Set of the process stoichiometric and kinetic parameters in ASM2d was used as a base point of further process calibration in newly developed comprehensive model Mantis2 for simulation study of "virtual" plant layout in GPS-x (Figure 2c).…”
Section: Resultsmentioning
confidence: 99%
“…Continual feedback between the model and real-time measurements (e.g. NH 4 -N and NO 3 -N and PO 4 -P behavior) from "Wschód" WWTP were additionally used to confirm initial modeling results. It was shown that a "well" calibrated model within an assessment study could be used to evaluate process capacities, operational changes, upgrades and/or process changes.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Phosphate adsorption above cellular capacity by PAOs is possible in enhanced biological phosphorus removal (EBPR). EBPR places the PAOs in alternating anaerobic and aerobic conditions (Zhou et al 2012;Drewnowski and Makinia 2014). Simultaneous removal of total phosphate (TP) and total nitrogen (TN) consumes organic matter.…”
Section: Introductionmentioning
confidence: 99%
“…The efficiency of EBPR is strongly dependent on the availability of appropriate carbon sources (Drewnowski and Makinia 2014). COD/P ratio affects the structure of bacterial communities involved in EBPR; however, majority of studies on PAO-GAO selection have been carried out on flocculent activated sludge as reviewed by Oehmen et al (2007).…”
Section: Introductionmentioning
confidence: 99%